Comparison of European Standard Patch Test Results of 330 Patients from an Occupational Diseases Hospital - Özge Gündüz; Aslı Aytekin; Engin Tutkun; Hınç Yılmaz (Dermatology Research and Practice)
Background and Aim. Contact dermatitis (CD) is the most prevalent occupational skin disease with a significant impact on quality of life. Patch testing is used for the identification of responsible allergens which may improve protective and preventive measures in the workplace. Herein, we aim to identify the demographic characteristics and occupation of patients with early diagnosis of occupational CD and compare patch test results. Materials and Methods. The study included 330 patients referred to our clinic between April 2009 and April 2011 and who were patch-tested with 28-allergen European Standard Test. Results. 126 (38%) patients were female and 204 (62%) were male with a mean age of 36.12 (±13.13) years. Positive allergic reactions were observed in 182 (55%) patients. Nickel sulphate (41/126) and potassium dichromate (39/204) were significantly the most common allergens in women and men, respectively (P<0.005). Additionally, the most common occupation in women was household activities (83/126) and in men was manufacturing (80/204). Conclusion. The allergens to which people become sensitized differ according to their working environment and occupation. Classification of occupations is important for identification of sensitization risks and monitoring of changes in allergen distribution of different occupations.